INTERAKSI MUSIKAL MELALUI GESTUR DAN VERBAL DALAM MUSIK JAZZ - Fabianus Deny Christianata Putra (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
ABSTRACT This paper explains a process of musical interaction in jazz music performances, on the performances of Solo Jazz Society musicians in Surakarta. The focus of this paper is about (1) how the process of musical interaction between Sojazz musicians occurs and (2) what factors cause musical interaction between Sojazz musicians. With the aim (1) to know how the process of musical interactions between Sojazz musicians occur and (2) to know the factors that cause the musical interactions between Sojazz musicians. The research method used is qualitative with descriptive analysis approach. n the performance, Sojazz musicians perform musical interactions between musicians through two forms of process. Gesture interactions that include eye contact, hand code, head jerking, lip reading and overall body posture are applied as cues while improvising. The second form of the process is through the musical interaction itself which is Accompaniment, melodic phrase and rhythmic motif, tension growth, and trade four. The process of musical interaction applied by Sojazz musicians as mentioned above, is through gesture used to create mutual interaction between musicians. Kata kunci : Solo Jazz Society, interaksi musikal jazz,